Mixed railway operations on the southern line of Thai railways: track utilization efficiency analysis - Taksaporn Thongboonpian; Waressara Weerawat; Jörn Pachl; Jeerapat Sang-iam (Transportation Research Interdisciplinary Perspectives, 2025)
This study examines the operational efficiency of Thailand’s Southern Railway Line under mixed-traffic conditions using the UIC 406 methodology and Timetable Planning Quality evaluation. The corridor integrates electric commuter and long-distance trains on shared tracks with different control systems and block configurations. The analysis shows that infrastructure design, particularly block length and signaling, significantly influences track utilization. A key contribution of this study is the integration of UIC 406 compression with travel time quotient (TTQ) to reveal inefficiencies in timetable structure. Findings indicate that short blocks support higher throughput despite greater train volumes, while long blocks lead to higher occupancy rates with fewer trains. The study proposes targeted improvements such as subdividing blocks and aligning timetables across train types. These measures can enhance efficiency without requiring new track construction. The results provide practical guidance for infrastructure planning and policymaking, offering a replicable approach for enhancing corridor performance under complex mixed-traffic conditions.